ChemInform Abstract: Exploring the in situ Utilization of Cyclic Imine Intermediates Generated by Isocyanoacetate Cycloaddition: Convergent Assembly of cis‐3a, 8a‐Hexahydropyrrolo[2, 3‐b]indole Scaffolds. Issue 7 (29th January 2015) - Huang, Lin; Cheng, Hengguang; Zhang, Runmei; Wang, Min; Xie, Chunsong
Abstract Hexahydropyrroloindoles are synthesized from isocyanoacetates and electron‐deficient olefins through a Cu(II) or Ag(I) catalyzed formal [3+2] cycloaddition, intramolecular nucleophilic addition, and protonation sequence.